2003
DOI: 10.1007/s00784-003-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of matrix molecules associated with wound healing following treatment with an enamel matrix protein derivative in humans

Abstract: Application of enamel matrix protein derivative (EMD) onto a debrided and conditioned root surface has been shown to promote periodontal regeneration in animals and humans. However, until now there is virtually no information from humans describing the expression of different matrix molecules in the newly formed periodontal tissues following treatment with EMD. This study investigated immunohistochemically in humans the expression of matrix molecules associated with periodontal tissues reformed after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
3
35
0
2
Order By: Relevance
“…In contrast to total collagen and collagen I, staining for collagen III was more intense in the control capsules, which is in agreement with the results of the study by Matsumoto et al (20). These results demonstrate a mechanism of contracture tissue formation that differs from that of wound healing, with increased levels of collagen type III (21,22). Similar to total collagen and collagen I, the levels of MMP-13 and MMP-1 were increased in the capsule of the ORC group compared with the CON group in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to total collagen and collagen I, staining for collagen III was more intense in the control capsules, which is in agreement with the results of the study by Matsumoto et al (20). These results demonstrate a mechanism of contracture tissue formation that differs from that of wound healing, with increased levels of collagen type III (21,22). Similar to total collagen and collagen I, the levels of MMP-13 and MMP-1 were increased in the capsule of the ORC group compared with the CON group in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, TIMP-13 was decreased in the control capsules compared with the contracted capsules. This high matrix turnover of joint capsule in the fibrotic joint capsule has also been reported in previous studies (21,22). An increase of pERK2 in rats with trauma-induced joint capsule fibrosis was observed in the present study, which may be responsible for these pathological alterations.…”
Section: Discussionsupporting
confidence: 89%
“…A variety of defect configurations has been surgically created in non-human primate dentitions, including palatal dehiscence (Laurell et al, 2006) and intrabony (Sculean et al, 1997(Sculean et al, , 2002, Class II-III furcation (Ripamonti et al, 2001;Hovey et al, 2006), and fenestration lesions (Sculean et al, 2000a(Sculean et al, , 2001. Fenestration defects typically heal spontaneously, due to the residual periodontal tissues whereby mesenchymal progenitor cells can easily repopulate the defect.…”
Section: Surgically Created Periodontal Defects In Non-human Primatesmentioning
confidence: 99%
“…Histological studies in animals have shown that a new layer of cementum with inserting fibers and new alveolar bone were formed when EMP was applied to a debrided and conditioned root surface. 5,15 These positive results in animals 17 were later confirmed by histological findings in humans 15 and by clinical improvement observed in controlled clinical trials. 3,7,8,10,13,19 Thus, the purpose of this study was to compare the results of periodontal clinical parameters after treatment of intrabony defects with open flap debridement (OFP) combined or not with enamel matrix protein (EMP).…”
Section: Introductionmentioning
confidence: 88%